11.9k views
0 votes
Solve: 6^2x-3 = 6^-2x+1
A. x= -1
B. x=0
C. x=1
D. x=4

2 Answers

2 votes

Answer:

C: x=1

Explanation:

User Juraj Michalak
by
4.3k points
1 vote

Answer:

C) x=1

Explanation:

The given equation is :

6^2x-3 = 6^-2x+1

In such type of equations where the base value is same on both the sides of the equation we can directly equate their powers. As on both the sides the base value is same i.e 6.

So, equating the power of 6


2x-3 = -2x+1


2x+2x =1+3


4x=4


x=1

By solving the equation we get x=1.

User BhalchandraSW
by
4.4k points